Leaders' individualized consideration, team commitment and patient loyalty: The role of social and task‐related contexts - Tang, Wei‐Gang; Stordeur, Sabine; Vandenberghe, Christian; D'hoore, William (Journal of occupational and organizational psychology, 2024)
Drawing from transformational leadership (TFL) theory and research on contextual leadership, we examined a conditional process model of leadership in nursing teams to predict patient loyalty. Using TFL's individualized consideration dimension as a salient facet of the construct in care services, we first posited that nurses' team affective commitment would partially mediate the impact of nurse leadership. We further conceptualized nurse–physician collaboration, organizational formalization and task feedback as discrete contexts that may curb the influence of head nurses' individualized consideration. In a three‐wave, multisource and multilevel study, we surveyed 654 nurses and 1770 patients from 91 hospital units. We found that team‐level head nurses' individualized consideration positively and partially related to patient loyalty through nurses' team commitment and that higher levels of nurse–physician collaboration, organizational formalization and task feedback were associated with reduced influence of individualized consideration on team commitment and patient loyalty. We discuss the implications of these findings for advancing theory and research on TFL and contextual factors of leadership.